Fibroblast-Like-Synoviocytes Mediate Secretion of Pro-Inflammatory Cytokines via ERK and JNK MAPKs in Ti-Particle-Induced Osteolysis - Ashish Ranjan Sharma (Materials, 2020)
Biomaterials are designed to replace and augment living tissues in order to provide functional support to skeletal deformities. However, wear debris produced from the interfaces of metal implants initiates inflammatory bone loss, causing periprosthetic osteolysis. Lately, fibroblast-like synoviocytes (FLS) have been shown to play a role in wear-debris-induced osteolysis. Thus, here we have tried to understand the underlying mechanism of FLS involvement in wear-debris-induced osteolysis. Our results demonstrate that the effects of Ti particle (1:100 cell-to-Ti particle ratio) on FLS can induce Cox-2 expression and activate NFkB signaling. Moreover, the mRNA expression of pro-inflammatory cytokines such as IL-6, IL-8, IL-11, IL-1β, and TNFα was found to be elevated. However, among these pro-inflammatory cytokines, the mRNA and protein levels of only IL-6, IL-1β, and TNFα were found to be significantly higher. Ti particles activated extracellular signal-regulated kinase (ERK) and c-Jun N-terminal kinase (JNK) mitogen-activated protein kinases (MAPKs) as an early response in FLS. Co-inhibition of ERK and JNK signaling pathways by their specific inhibitors (PD9805 and SP600125, respectively) resulted in the suppression of mRNA and protein levels of IL-6, IL-1β, and TNFα in FLS. Taken together, targeting ERK and JNK MAPKs in FLS might provide a therapeutic option for reducing the secretion of bone-resorbing pro-inflammatory cytokines, thus preventing periprosthetic osteolysis.